Penghapusan Presidential Threshold dalam Perspektif Imam al-Mawardi (Analisis Putusan Mahkamah Konstitusi Nomor 62/PUU-XXII/2024) - Rizky Ahadyan Ardyansyah (Jurnal Hukum Lex Generalis, 2025)
The abolition of the Presidential Threshold through Constitutional Court Decision No. 62/PUU-XXII/2024 has sparked debate over political justice and governmental stability. This study analyzes the issue through Imam Al-Mawardi’s perspective on state politics, focusing on leadership, political legitimacy, and the principle of public interest (maslahah). Using a normative legal method with conceptual and case approaches, the findings reveal that removing the threshold risks producing leaders with weak legitimacy, while maintaining an excessively high threshold creates political injustice. The ideal position is to establish a proportional threshold aligned with maslahah and substantive justice.